Languages of truth : essays 2003-2020 - Rushdie, Salman (b, 2021)
Salman Rushdie is celebrated as a storyteller of the highest order, illuminating deep truths about our society and culture through his gorgeous, often searing, prose. Now, in his latest collection of nonfiction, he brings together insightful and inspiring essays, criticism, and speeches that focus on his relationship with the written word, and solidify his place as one of the most original thinkers of our time. Gathering pieces written between 2003 and 2020, Languages of Truth chronicles Rushdie's own intellectual engagement with a period of momentous cultural shifts. Immersing the reader in a wide variety of subjects, he delves into the nature of storytelling as a deeply human need, and what emerges is, in myriad ways, a love letter to literature itself. Rushdie explores what the work of authors from Shakespeare and Cervantes to Samuel Beckett, Eudora Welty, and Toni Morrison mean to him, often by telling vivid, sometimes humorous stories of his own personal encounters with them, whether on the page or in person. He delves deeper than ever before into the nature of "truth," revels in the vibrant malleability of language, and the creative lines that can join art and life, and he looks anew at migration, multiculturalism and censorship. The ideas, true stories, and arguments presented here are at once revelatory, funny, and eye-opening, enlivened on every page by Rushdie's signature wit and dazzling voice, making this volume a genuine pleasure to read. Languages of Truth offers the author's most piercingly analytical views yet on the evolution of literature and culture even as he takes us deep into his own exuberant and fearless imagination.
Keywords: y; Speeches, addresses, etc., English; Creative nonfiction, English